Intelligent Manufacturing and Mechatronics : Springer Proceedings in Materials - Radhiyah, Abd Aziz (Springer Nature Singapore, 2024)
This book showcases a portion of the iM3F 2023 conference proceedings, focusing on the recent advancement in sustainable manufacturing and materials. It emphasizes recent progress, significant advancements, and challenges to the materials science and engineering community, along with the emergence of intelligent manufacturing engineering and technology while addressing the UN Sustainable Development Goals. The book discusses both traditional and advanced approaches used in various sustainable manufacturing and materials applications. Readers can expect to gain a comprehensive understanding of current trends, challenges, solutions, and mitigating factors from this publication.